CULTURAL TRANSFER IN THE TRANSLATIONS OF MEDIA ORGANIZATION WEBSITES: A DESCRIPTIVE ANALYSIS OF ARTICLES AND THEIR TURKISH TRANSLATIONS ON THE BBC WEBSITE - Özge Aksoy; Zekiye Müge Tavil (Informascope, 2017)
The websites of media organizations address to readers from many different languages and cultures. Each culture has its own specific values, habits and norms. Translators employ some translation strategies in order to transfer these culture specific items (hereinafter; CSIs) from a source text (hereinafter; ST) to a target text (hereinafter; TT). They are supposed to establish translations that are completely comprehensible for the target readers. In this study, the articles of the British Broadcast Company (hereinafter; the BBC) that are translated by BBC Turkish Service translator and published in the link 'Dergi' are analysed based on Toury's translational norms and Aixela's classification for CSIs. It is designed with a qualitative method and supported with an interview to triangulate the data. The findings show that the translations are generally 'acceptable', that is, the translator has the tendency towards target culture according to Toury' s translational norms. She mostly employs constitution strategies of Aixela to transfer CSIs and this indicates the general tendency of the translations to 'be a representation of a source text'. However, the translator specifies the target readers of the link as 'educated young population' and this does not complicate the comprehensibility of the CSIs by the target readers. Keywords: Translation Studies, Translational Norms of Toury, Cultural Transfer, Culture Specific Items, Aixela, BBC Turkish Service